Rainfall-runoff simulation of Sg. Kuantan upstream (Kenau Flow Station) using HEC-HMS - Rubeni, Raja (2017)
Flood during monsoon season, not only affects the urbanised catchment, also affects the rural area. Hence, a study must conducted to avoid the crisis of damage due to flood in surrounding of rural area. Kenau Flow Station is a stream river station that separated from upper part of large Kuantan River. A study for predict rainfall-runoff of Sg. Kuantan using Hydrologic Engineering Centre-Hydrologic Modelling System (HEC-HMS) was preferred as calibrated & validated gauged station. The rainfall runoff simulation was very important in flood studies as it characterize storm water runoff. Hydrologic Engineering Centre-Hydrologic Modelling System (HEC-HMS) was selected for stimulation as considered as best application of water resources and easiest method to analyse and predict flow of rainfall-runoff of Sg. Kuantan upstream. This Study aims to look at two transformation methods available in HEC-HMS for effective rainfall to the outlet. Snyder and Clark Time Area method were used to stimulate the flow of river basin. Hence, rainfall and stream flow data were obtained from Department of Irrigation and Drainage of 2011 for Bukit Kenau station. The data used were rainfall data and stream flow data. The data was obtained using 4 rainstorm events, 1st event for calibration and 3 more for validation from year 2011. SCS Curve Number in HEC-HMS used to determine the losses of rainfall. Predicted Curve Number for rural area is 70 and percentage of impervious area is 10%. The time of concentration and storage coefficient for Clark method are 7.5 hour and 5.5 hour. Hence, for Snyder method, time of peak and peaking coefficient are 6.5 hour and 0.6. The Efficiency index (EI) was used to identify accuracy of result that simulated. EI for Clark is 80.69 whereas for Snyder is 83.86 %. From the simulation, the best method for rainfall and runoff analysis for Kenau Flow Station is Snyder method.